Artificial Intelligence Shaping Talent Intelligence and Talent Acquisition for Smart Employee Management - Agnihotri, Alka; Pavitra, K. H.; Balusamy, Balamurugan; Maurya, Alka; Bibhakar, Pratyush (EAI Endorsed Transactions on Internet of Things, 2023)
INTRODUCTION: Due to the increased importance of artificial intelligence (AI) in talent intelligence (TI), and TI in talent acquisition (TA), this paper shows how AI improves the TI and consequently, the TA process of an organization.OBJECTIVES: The objectives of this paper are to understand the evolution of AI-driven TI concepts and explore the role of AI in TI.METHODS: Primary and secondary data were used for research and analysis was performed using SPSS. Primary data was collected through a survey of 20 HR managers from 20 companies in Delhi-NCR. These 20 managers were selected through random sampling method and from them the data on role of AI in TI and TA was collected using a questionnaire. Secondary data through literature review was used to explore TI.RESULTS: The paper not only brings out the role of AI in TI, but also elaborates the TI concept. From the survey data of HR managers, and secondary data, it is understood that AI contributes to TI of an organization, which helps in making TA more effective and efficient.CONCLUSION: AI enables better TI, which improves TA processes of an organization Thus, AI contributes to the TA of an organization.
Keywords: TI; Talent Intelligence; TA; Talent Acquisition; AI; Artificial Intelligence; ATS; Application Tracking System; Smart Employee Management